PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT JAYATAMA SELARAS - Sugiyanto dan Febri Diani (Fakultas Ekonomi Universitas Borobudur, 2015)
This study aims to determine the influence of leadership style and motivation on employee productivity at PT Jayatama Selaras. The data used in this study is primary data collected from the results of distributing questionnaires conducted at PT Jayatama Selaras, the method of data processing using path analysis method (Path Analysis) using SPSS application program version 22, and the sample used as many as 75 people.The results showed that there is a positive and significant influence between leadership style and motivation on work productivity. This is evidenced from the results of previous statistical tests. And from the test results also confirmed that motivation mediates some of the leadership style to work productivity. Keywords: Leadership Style, Motivation, Employee Productivity.